Community disassembly and invasion of remnant native grasslands under fluctuating resource supply - Tognetti, Pedro Maximiliano (2014)
1. Native vegetation fragments embedded in anthropogenic landscapes are increasingly threatened by land-use intensification. Managing disturbance regimes and nutrient inputs may help maintain species diversity in such remnants. Yet it is unclear the extent to which changes in resource availability due to reduced capture by resident plants and/or increased supply rates may trigger native community disassembly and exotic invasions. 2. We examined how mowing disturbance and N fertilizer addition affected plant community recovery after a burning event in a remnant corridor of tussock pampa grassland in Argentina. The percentage cover and richness of native and exotic plant functional groups were monitored over four years. According to the ?fluctuating resource theory?, we expected invasion to be highest when both light and N availability were increased simultaneously. 3. Mowing delayed recovery by dominant C4 tussock grasses and promoted subordinate, native C3 grasses and exotic legumes, thus enhancing both native and exotic species richness. Fertilization induced a transient increase in native forbs but decreased total plant richness. Moreover, N addition to mowed grassland led to rapid invasion by short-lived exotic forbs, which were then replaced by exotic perennial grasses. Exotic grasses eventually spread across the grassland corridor, although at different rates depending on the treatment, and in parallel to a generalized decline in native species cover. 4. Synthesis and applications. Community disassembly patterns reflected differential responses of native and exotic functional groups to altered resource supply rates. Synergisms between canopy disturbances and N enrichment posed the greatest threat to preserving a pampa grassland remnant prone to invasion. Establishing buffer zones may be required to enhance the viability of corridor-like grassland remnants in agricultural landscapes.